The Effectiveness Of Foot Massage Therapy On Reducing Edema And Improving Sleep Quality In Patients With Congestive Heart Failure (CHF) - Delvin Dananjaya; Amrih Widiati (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Background: Congestive Heart Failure (CHF) is a complex clinical syndrome characterized by the heart's inability to pump blood adequately, causing various clinical manifestations, including lower extremity edema and sleep disturbances. One non-pharmacological intervention that can be given to help overcome this problem is foot massage therapy. Objective: To analyze the effectiveness of foot massage therapy on reducing edema and improving sleep quality in Congestive Heart Failure (CHF) patients at KRMT Wongsonegoro Regional Hospital, Semarang. Method: This study used a descriptive method with a case study approach in two Congestive Heart Failure (CHF) patients, namely Mr. A and Mrs. S. Data collection was carried out through observation, interviews, and secondary data. The instruments used included an observation sheet, a pitting edema scale, and a sleep quality assessment sheet using the Pittsburgh Sleep Quality Index (PSQI). The intervention in the form of foot massage therapy was given for two days with a duration of 15–20 minutes per session. Results: After foot massage therapy, Mr. A experienced a decrease in edema from grade +3 to +2, while Mrs. S experienced a decrease in edema from grade +2 to +1. The sleep quality of both patients also improved, indicated by a reduction in the frequency of nighttime awakenings and an increase in sleep duration. Mr. A experienced an increase in sleep duration from ±4 hours to ±6 hours, while Mrs. S experienced an increase from ±5 hours to ±7 hours. Conclusion: Foot massage therapy is effective in helping reduce lower extremity edema and improving sleep quality in patients with Congestive Heart Failure (CHF). This intervention can be used as a non-pharmacological complementary therapy in providing comprehensive nursing care to CHF patients